'I'm not racist; my high school was diverse!' white preservice teachers deploy diversity in the classroom. Issue 2 (3rd July 2017) - Pezzetti, Karen
Abstract: This study employs ethnographic methods to explore the ways that white American preservice teachers in two different Social Contexts of Education classes conceptualise diversity and use this term to accomplish discursive goals. Data collected from observation notes, interviews and written assignments suggest that participants simultaneously seemed to ascribe positive value judgements to their own experiences in racially diverse environments yet ascribe negative value judgments to the potential diversity of their hypothetical future students. Participants voiced abstract commitments to diversity in order to position themselves as good, non-racist people; however, these positive endorsements of diversity did not extend to appreciation of the potential racial diversity of their future students. The data suggest that although participants have learned to engage in a discourse that celebrates diversity, at least on abstract terms, they may still lack key understandings fundamental to providing effective instruction to all students.